Legality of General Practitioners in Practicing Acupuncture - Winata, Eurika; Nugraheni, Ninis; Nugroho, Hari Pudjo (CV. Publikasi Indonesia, 2025)
Regulations for acupuncture practice in Indonesia are based on Law No. 17 of 2023 concerning health and Permenkes No. 34 of 2018 concerning license and practice regulation of acupuncture therapists. In Indonesia, acupuncture treatment consists of traditional acupuncture done by acupuncture therapists and medical acupuncture done by doctors, both acupuncture specialists and general practitioners. This research titled